2015
DOI: 10.5230/jgc.2015.15.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Modified Laparoscopy-Assisted Proximal Gastrectomy Compared to Conventional Proximal Gastrectomy or Total Gastrectomy for Upper-Third Early Gastric Cancer with Special References to Postoperative Reflux Esophagitis

Abstract: PurposeThis study evaluated the functional and oncological outcomes of proximal gastrectomy (PG) in comparison with total gastrectomy (TG) for upper-third early gastric cancer (EGC).Materials and MethodsThe medical records of upper-third EGC patients who had undergone PG (n=192) or TG (n=157) were reviewed. The PG group was further subdivided into patients who had undergone conventional open PG (cPG; n=157) or modified laparoscopy-assisted PG (mLAPG; n=35). Patients who had undergone mLAPG had a longer portion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
2
31
1
Order By: Relevance
“…The main reason for the number of lymph nodes less than 25 in both groups can be explained by that D1 dissection was applied to seven patients in the TG group and to five patients in the PG group because the intraoperative determination of small peritoneal metastases could not be detected preoperatively with imaging methods. In the literature, many studies have demonstrated that although fewer lymph nodes have been harvested in the PG than the TG, no statistically significant difference was found between the two surgical procedures regarding survival rates; the extent of resection has not affected the outcome once adequate resection margins have been reached (7,9,16,17). The results of these studies were harmonious with our manuscript.…”
Section: Discussionsupporting
confidence: 79%
“…The main reason for the number of lymph nodes less than 25 in both groups can be explained by that D1 dissection was applied to seven patients in the TG group and to five patients in the PG group because the intraoperative determination of small peritoneal metastases could not be detected preoperatively with imaging methods. In the literature, many studies have demonstrated that although fewer lymph nodes have been harvested in the PG than the TG, no statistically significant difference was found between the two surgical procedures regarding survival rates; the extent of resection has not affected the outcome once adequate resection margins have been reached (7,9,16,17). The results of these studies were harmonious with our manuscript.…”
Section: Discussionsupporting
confidence: 79%
“…Previous retrospective studies have documented that distal gastrectomy has advantages over TG in postoperative nutritional status and quality of life [30][31][32]. On the other hand, it has been reported that PG is better than TG in terms of body weight loss and postoperative symptoms such as diarrhea and dumping syndrome [7,11,33]. In the present study, however, nutritional status after LPG was poor or equal to that after LTG.…”
Section: Discussioncontrasting
confidence: 63%
“…On the other hand, PG has several benefits compared to TG in terms of maintaining gastric hormones and gastric acid production resulting from preservation of the gastric antrum. However, reflux esophagitis is common after PG, and although various reconstruction methods have been suggested to reduce this problem, no standard procedure has yet been established [5,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic meta-analysis comparing TG with PG, PG with esophagogastrostomy showed a higher incidence of reflux esophagitis and anastomotic stenosis [ 88 ]. However, several positive results of LPG with modified reconstruction methods have been reported [ 48 , 89 ]. Accordingly, LPG can be considered an attractive treatment option for proximal EGC as a minimally invasive surgery to preserve functionality, including reduction of postoperative complaints, prevention of anemia, improved nutrition, and improved production of gut hormones [ 90 – 93 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%